Advance in oral delivery systems for therapeutic protein. (16th March 2019) - He, Shiming; Liu, Zhongcheng; Xu, Donggang
Abstract: Oral delivery is the most common method of drug administration with high safety and good compliance for patients. However, delivering therapeutic proteins to the target site via oral route involves tremendous challenge due to unfavourable conditions like biochemical barrier, mucus barrier and epithelial barriers. According to the functional differences of various protein drug delivery systems, the recent advances in pH responsive polymer-based drug delivery system, mucoadhesive polymer-based drug delivery system, absorption enhancers-based drug delivery system and composite polymer-based delivery system all were briefly summarised in this review, which not only clarified the clinic potential of these novel drug delivery systems, but also described the way for increasing oral bioavailability of therapeutic protein.